2013
DOI: 10.1177/0363546513493589
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of 16,192 Anterior Cruciate Ligament Reconstructions From a Community-Based Registry

Abstract: Large, community-based ACLRRs are useful in informing participating surgeons of current treatment practices, prevalence of concurrent injuries, and outcomes associated with the procedures. Information from the ACLRR can be used to develop interactive patient and surgeon tools that can be used to optimize patient care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
157
0
13

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 160 publications
(178 citation statements)
references
References 22 publications
8
157
0
13
Order By: Relevance
“…13 Other databases report higher female percentages for primary reconstructions 11 and lower percentages of females with regard to primary and revision reconstructions. 6,12 Younger patients had a higher rate of revisions and bilateral reconstructions, thereby confirming previous studies. 2,6,7,13 Previous reports from the Swedish ACL Register have reported a higher rate of re-reconstruction for the specific group of females who sustained their injury playing soccer.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…13 Other databases report higher female percentages for primary reconstructions 11 and lower percentages of females with regard to primary and revision reconstructions. 6,12 Younger patients had a higher rate of revisions and bilateral reconstructions, thereby confirming previous studies. 2,6,7,13 Previous reports from the Swedish ACL Register have reported a higher rate of re-reconstruction for the specific group of females who sustained their injury playing soccer.…”
Section: Discussionsupporting
confidence: 86%
“…6,12 Younger patients had a higher rate of revisions and bilateral reconstructions, thereby confirming previous studies. 2,6,7,13 Previous reports from the Swedish ACL Register have reported a higher rate of re-reconstruction for the specific group of females who sustained their injury playing soccer. 2 Walden et al showed that ACL injuries can be prevented in adolescent female soccer players after introducing an injury prevention program.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…During the same period, approximately 5-6% will sustain a contralateral ACL rupture (Ahlden et al, 2012;Crawford, Waterman, & Lubowitz, 2013;Hettrich, Dunn, Reinke, Group, & Spindler, 2013;Lind, Menhert, & Pedersen, 2012;Salmon, Russell, Musgrove, Pinczewski, & Refshauge, 2005;Shelbourne, Gray, & Haro, 2009;Spindler et al, 2013). Young age (Ahlden et al, 2012;Faltstrom, Hagglund, Magnusson, Forssblad, & Kvist, 2014;Hettrich et al, 2013;Kvist, Kartus, Karlsson, & Forssblad, 2014;Lind et al, 2012;Magnussen et al, 2012;Maletis, Inacio, & Funahashi, 2013;Shelbourne et al, 2009;Wasserstein et al, 2013;Webster, Feller, Leigh, & Richmond, 2014) and returning to high activity level after an ACL injury (Borchers, Pedroza, & Kaeding, 2009;Faltstrom, Hagglund, & Kvist, 2013;Salmon et al, 2005;Shelbourne et al, 2009;Sward et al, 2010) have been highlighted as the most important risk factors for sustaining a contralateral ACL injury or an ACL graft rupture. Age may be a proxy for neuromuscular maturation, and altered neuromuscular control of the knee and hip and impaired postural stability has been reported to predict a second ACL injury (Paterno et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…7,29 Only 2 studies that reported low SSI rates were from multiple institutions. Maletis et al 21 reported an overall SSI rate of 0.46% (0.3% deep SSI, 0.1% superficial SSI), using a Kaiser Permanente registry, with all outcomes verified by chart review. Jameson et al 20 utilized data from the English National Health Service and reported a rate of 0.25% for deep infection within 30 days and 0.75% for wound complication (infection and hematoma), but identification of complications relied solely on hospital readmissions.…”
Section: Discussionmentioning
confidence: 99%